2006
DOI: 10.1016/j.canlet.2005.07.029
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic aromatic hydrocarbon-DNA adduct formation in prostate carcinogenesis

Abstract: The evidence for polycyclic aromatic hydrocarbons (PAH) playing a role in prostate carcinogenesis comes mainly from associations between reported PAH exposures and prostate cancer in epidemiologic studies. Associations between prostate cancer and DNA repair genotypes and phenotypes have also been reported, lending further credence to a PAH-induced carcinogenesis pathway in prostate cancer. Recent work that demonstrates the human prostate has metabolic enzyme activity necessary for PAH activation and will form … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 67 publications
0
35
3
Order By: Relevance
“…Previous studies demonstrated that DNA adducts are formed in the prostate tissue as a result of exposure to oxidative stress and environmental toxins (Rybicki et al, 2006;Tang et al, 2007), and DNA repair mechanisms play an important role in removal of oxidative DNA compounds or DNA adducts from damaged genomic DNA sites. However, polymorphisms in DNA repaired genes play a critical role in altering the function of repairing DNA damages and removal of oxidative DNA compounds or DNA adducts.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that DNA adducts are formed in the prostate tissue as a result of exposure to oxidative stress and environmental toxins (Rybicki et al, 2006;Tang et al, 2007), and DNA repair mechanisms play an important role in removal of oxidative DNA compounds or DNA adducts from damaged genomic DNA sites. However, polymorphisms in DNA repaired genes play a critical role in altering the function of repairing DNA damages and removal of oxidative DNA compounds or DNA adducts.…”
Section: Discussionmentioning
confidence: 99%
“…The hydroxylation of PAHs causes an increased affinity toward DNA and proteins and formation of adducts. Elevated levels of adducts can be a cause of protein damage and mutation that can lead to carcinogenesis in various organs (ATSDR 1995;Gaspari et al 2003;Rybicki et al 2006;Bosetti et al 2007;Sagiv et al 2009;Herbstman et al 2012). Therefore, some priority PAHs has been classified as probable carcinogens and a few others as possible carcinogens to humans (IARC 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Among various contaminants, considerable attention has been emphasized on remediation of polycyclic aromatic hydrocarbons (PAHs), as they are either known or suspected carcinogens and mutagens [8,9]. Moreover, their low aqueous solubility and high affinity to soils give rise to their persistence in the environment.…”
Section: Introductionmentioning
confidence: 99%